2021
DOI: 10.17957/ijab/15.1824
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Genetic Variability and Direct-Indirect Contribution of Post-Anthesis Traits to the Grain Yield in Bread Wheat (Triticum aestivum) at Different Sowing Dates

Abstract: In cotton-wheat cropping system of Pakistan, sowing of wheat is delayed which results in a heavy loss to the farmers. To this end, a two-year field experiment was conducted to i) asses the performance of genotypes under late sowing ii) heritability and genetic association of different traits under normal and late sowing for their use in the breeding programs. Experimental factors included 20 diverse wheat genotypes (16 advance lines and 04 approved varieties) factorially combined with two sowing dates i.e., no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
2
2
0
Order By: Relevance
“…Based on these categories traits such as days to heading (97.51%), Hectoliter Weight (93.30%), days to maturity (92.60%), biomass yield (91.88%), peduncle length (89.17%), grain yield (86.87%), Thousand Kernel Weight (86.69%, plant height (85.89%) and yield per head (82.57%) had very high broad sense heritability. Similar result were documented that high estimates of heritability for days to heading, days to maturity and plant height (Rajput et al, 2019, Upadhyay et al, 2019, and 1000 kernel weight (Fikre et al, 2015, Kabir et al, 2017, biomass yield (Muhammad et al, 2017;Atinafu et al, 2020, Sami et al, 2021 and also high heritability was noticed for peduncle length ( Upadhyay et al, 2019). similarly high heritability for biomass yield and grain yield (Sami et al, 2021) and high heritability for yield head -1 (Mohant et al, 2016) and for peduncle length (Muhammad et al, 2017, Muhammad et al, 2021.…”
Section: Estimation Of Heritability and Genetic Advancesupporting
confidence: 76%
See 1 more Smart Citation
“…Based on these categories traits such as days to heading (97.51%), Hectoliter Weight (93.30%), days to maturity (92.60%), biomass yield (91.88%), peduncle length (89.17%), grain yield (86.87%), Thousand Kernel Weight (86.69%, plant height (85.89%) and yield per head (82.57%) had very high broad sense heritability. Similar result were documented that high estimates of heritability for days to heading, days to maturity and plant height (Rajput et al, 2019, Upadhyay et al, 2019, and 1000 kernel weight (Fikre et al, 2015, Kabir et al, 2017, biomass yield (Muhammad et al, 2017;Atinafu et al, 2020, Sami et al, 2021 and also high heritability was noticed for peduncle length ( Upadhyay et al, 2019). similarly high heritability for biomass yield and grain yield (Sami et al, 2021) and high heritability for yield head -1 (Mohant et al, 2016) and for peduncle length (Muhammad et al, 2017, Muhammad et al, 2021.…”
Section: Estimation Of Heritability and Genetic Advancesupporting
confidence: 76%
“…Similar result were documented that high estimates of heritability for days to heading, days to maturity and plant height (Rajput et al, 2019, Upadhyay et al, 2019, and 1000 kernel weight (Fikre et al, 2015, Kabir et al, 2017, biomass yield (Muhammad et al, 2017;Atinafu et al, 2020, Sami et al, 2021 and also high heritability was noticed for peduncle length ( Upadhyay et al, 2019). similarly high heritability for biomass yield and grain yield (Sami et al, 2021) and high heritability for yield head -1 (Mohant et al, 2016) and for peduncle length (Muhammad et al, 2017, Muhammad et al, 2021.…”
Section: Estimation Of Heritability and Genetic Advancesupporting
confidence: 76%
“…Bhanu et al ( 2018) also observed a significant positive correlation between plant height and spike length in their study. Ul-Allah et al (2021) identified noteworthy associations between the plant height and a number of spikelets. The remaining traits showed a non-significant association with number of tillers plant -1 (Table 1).…”
Section: Resultsmentioning
confidence: 97%
“…Heritability is essential to study for the degree of transmission of traits to future generations in any breeding program [ 45 , 46 ]. Although high broad-sense heritability for almost all the traits were observed under all fertilization conditions, there were some differences which might be due to variation in the variability under different fertilization conditions.…”
Section: Discussionmentioning
confidence: 99%